2014
DOI: 10.1007/s15010-014-0656-7
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal pathogens detected by multiplex nucleic acid amplification testing in stools of pediatric patients and patients returning from the tropics

Abstract: Our study demonstrates broad detection of relevant gastroenteritis pathogens by multiplexNAT with a short turnaround time. This is important for diagnosis, infection control and empiric management of gastroenteritis patients, but may be selectively complemented by bacterial culture and resistance testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 39 publications
1
31
1
1
Order By: Relevance
“…In addition, the xTag GPP assay identified coinfections in 9.5% (n ϭ 86) of positive samples, with C. difficile, norovirus, and Campylobacter being present in Ͼ25% of samples that had 2 or more pathogens detected (12). These data are similar to other studies that have evaluated the performance of the Luminex xTag GPP assay, which have also demonstrated that the Luminex GI panel increases both the positivity rate and the number of coinfections detected compared to conventional methods (13)(14)(15).…”
Section: How Do Multiplex Molecular Tests Perform Compared To Conventsupporting
confidence: 84%
“…In addition, the xTag GPP assay identified coinfections in 9.5% (n ϭ 86) of positive samples, with C. difficile, norovirus, and Campylobacter being present in Ͼ25% of samples that had 2 or more pathogens detected (12). These data are similar to other studies that have evaluated the performance of the Luminex xTag GPP assay, which have also demonstrated that the Luminex GI panel increases both the positivity rate and the number of coinfections detected compared to conventional methods (13)(14)(15).…”
Section: How Do Multiplex Molecular Tests Perform Compared To Conventsupporting
confidence: 84%
“…However, microscopic examination reported a 23% Blastocystis hominis in adult travelers which is not covered by the xTAG GPP. All positive calls by xTAG GPP for Adenovirus, Rotavirus, Clostridium difficile and Cryptosporidium were confirmed, but not all positive calls for Norovirus and Giardia were confirmed 77 . In the study reported by Claas EC et al the Nororvirus performance of xTAG GPP is comparable to real-time PCR, with a 100% sensitivity and specificity for Norovirus GI and 92.5% sensitivity and 97.6% specificity for Norovirus GII.…”
Section: Current Enteric Multiplex Commercial Assaysmentioning
confidence: 89%
“…Other extraction platforms include Roche’s MagNA Pure 75 . Qiagens EZ1 virus mini kit 76 , Qiagen’s QIAsymphony 40 , and Abbott m2000sp instrument 77 .…”
Section: Current Enteric Multiplex Commercial Assaysmentioning
confidence: 99%
“…In a study by Beckmann et al using xTAG GPP testing on samples from pediatric patients presenting with symptoms of acute gastrointestinal disease, 7% were positive for C. difficile, 39% of which were from patients Ͻ1 year of age. The authors did not provide any further data regarding whether the detection of C. difficile correlated with CDI in these infants, but they did question whether the finding of C. difficile in this setting warrants treatment (45). In another study where xTAG GPP was used as the first line of detection of gastrointestinal pathogens in 211 prospectively collected specimens from a pediatric hospital, C. difficile was the number one pathogen detected (10.9%).…”
Section: Difficile Diagnostic Testsmentioning
confidence: 98%